Sensing the Spirits: The Healing Dramas and Poetics of Brujería Rituals - Romberg, Raquel (Anthropologica, 2012)
Following the path suggested by Joseph Murphy more than a decade ago, this paper explores the sensuous spiri tuality of healing rituals in Puerto Rican brujeria, stressing their performative, embodied nature and significance. Carefully crafted gestures, meticulously manipulated objects, poetically strung words, and before spiritually inspired music and dance create dramatic experiences. The voices of Spiritist entities, Santeria orishas, and the recently dead reveal sources of af flictions and solutions in a totalizing, emotional event involving all the senses. This is where healing begins. The interpersonal, present-oriented pragmatic space that emerges during brujeria ritual challenges notions about the centrality of belief in healing rituals.